Baltų moderniųjų tautų genezė ir bajorija XVIII a. pab. - XIX a. pirmojoje pusėje lyginamosios analizės aspektu - Pivoras, Saulius (Lietuvos istorijos studijos, 1997)
This article applies a comparative method for studying the role of the nobility in the formation of modern Baltic nations in order to elucidate the factors, which determined role differences. Noble attitudes to ethnosocial changes, changes of ethnopolitical self-consciousness of nobility and the position of nobility in the emergence of national cultures are scrutinized. As it follows from the comparison, deconstruction of the feudal social system in Lithuania made the nobility turn their attention to the peasantry and to common interests and common origins, to find out ethnogenetical community. The lack of it in relations of the Baltic Germans with the Latvians was an obstacle in the ethnosocial harmonization. In the development of ethnopolitical self-consciousness of the Lithuanian nobility, the main political concept was that of a "nation-state," while in the Baltic Germans' nobility case it was the concept of an "estate-nation." Baltic Germans clearly defined their national identity, even if with certain estate and historical prejudices, and they never wanted to recognize Latvian culture as their own. Lithuanian nobility, on the contrary, showed some willingness to include people's culture into a common cultural perspective. It seems that the major factor in determining the different roles of Lithuanian and Baltic German nobility in ethnonational processes was the ethnogenetical memory.